Examining the Dorsolateral and Ventromedial Prefrontal Cortex Involvement in the Self-Attention Network: A Randomized, Sham-Controlled, Parallel Group, Double-Blind, and Multichannel HD-tDCS Study - Martínez-Pérez, Víctor; Campoy, Guillermo; Palmero, Lucía B.; Fuentes, Luis J. (Frontiers in Neuroscience, 2020)
Background: Attention and perception are strongly biased towards information about oneself compared to information about others. The self-attention network, an integrative theoretical framework for understanding the self-prioritization effects (SPE), proposes that the ventromedial prefrontal cortex (VMPFC) and the posterior superior temporal sulcus (pSTS) are the two nodes responsible for the preferential processing of self-related stimuli, which interact with the attentional control network (associated with the dorsolateral prefrontal cortex, DLPFC), responsible for processing others-related stimuli. So far, neuroimaging studies have provided considerable correlational evidence supporting the self-attention network. Objective: Here we went beyond correlational evidence by manipulating cortical activity using high definition transcranial direct current stimulation (HD-tDCS), a non-invasive brain stimulation method. We assessed whether anodal and cathodal stimulation of the VMPFC or the DLPFC modulate the processing of self and others related stimuli. Methods: We used an associative unbiased learning procedure, the so-called shape-label matching task, to assess the SPE in a sample of N = 90. We accomplished to overcome different methodological weaknesses of previous studies using different multichannel montages for excitatory and inhibitory effects over both the VMPFC and the DLPFC. Results: We found no effect of shape association for non-matching pairs, whereas there was an effect of shape association in the matching condition. Performance (reaction times and accuracy) was better for the self-association than for the other two associations, and performance for the friend-association was better than for the stranger-association. Thus, we replicated the self-prioritization effect (SPE) with behavioral data. At the neural level, none of the stimulation succeeded to modulate the magnitude of the SPE effect. Conclusion: We discuss the implications of these findings, in particular why cognitive modeling theories about self-prioritization effects should favor an epiphenomenal rather than a causal link between VMPFC/DLPFC and the impact of personal significance stimuli on perception.